Data security in genomics: A review of Australian privacy requirements and their relation to cryptography in data storage - Arran Schlosberg (Elsevier, 2016)
The advent of next-generation sequencing (NGS) brings with it a need to manage large volumes of patient data in a manner that is compliant with both privacy laws and long-term archival needs. Outside of the realm of genomics there is a need in the broader medical community to store data, and although radiology aside the volume may be less than that of NGS, the concepts discussed herein are similarly relevant. The relation of so-called "privacy principles" to data protection and cryptographic techniques is explored with regards to the archival and backup storage of health data in Australia, and an example implementation of secure management of genomic archives is proposed with regards to this relation. Readers are presented with sufficient detail to have informed discussions - when implementing laboratory data protocols - with experts in the fields.